Future Trends in Synthetic Biology—A Report - El Karoui, Meriem; Hoyos-Flight, Monica; Fletcher, Liz (Frontiers in Bioengineering and Biotechnology, 2019)
Leading researchers working on synthetic biology technologies and their applications gathered at the University of Edinburgh in May 2018 to discuss the latest challenges and opportunities in the field. In addition to the potential socio-economic benefits of synthetic biology, they also examined the ethics and security risks arising from the development of these technologies. Speakers from industry, academia and not-for-profit organisations presented their vision for the future of the field and provide guidance to funding and regulatory bodies to ensure that synthetic biology research is carried out responsibly and that it realises its full potential. This report aims to capture the collective views and recommendation that emerged from the discussions that took place. The meeting was held under the Chatham House Rule to promote open discussion; the findings and quotes included in the report are therefore not attributed. The goal of the meeting was to identify research priorities and bottlenecks. It also provided the opportunity to discuss how best to manage risk and earn public acceptance of this emerging and disruptive technologies.